Preparation of Si-SiOx nanoparticles from volatile residue produced by refining of silicon. (1st February 2019) - Gan, Chuanhai; Wen, Shutao; Liu, Yingkuan; Wen, Weidong; Dou, Peng; Su, Jing; Luo, Xuetao
Highlights: Residual Si is recycled to prepare Si-SiOx nanoparticles. Si-SiOx nanoparticles as anode materials have good electrochemical performances. Water is a key role to obtain Si-SiOx nanoparticles. Deposition pattern of residual Si agrees with model of three-dimension growth. Abstract: Residual Si was produced on a furnace wall when upgraded metallurgical grade Si was refined by electron beam melting. It was then recycled to prepare Si-SiOx nanoparticles with an average size of 100 nm by planetary ball milling. The obtained Si-SiOx nanoparticles mainly consist of amorphous Si, crystalline Si and amorphous SiOx, which was confirmed by XRD, FTIR, XPS and TEM. SiOx is mainly composed of SiO2 and SiO1.35 . Distilled water used as a grinding aid not only enhances milling efficiency, but also plays a key role in obtaining SiOx . During refining of upgraded metallurgical grade Si, the deposition pattern of residual Si on furnace wall agrees with model of three-dimension growth. Growth of Si-SiOx nanoparticles is the mutual effect of distilled water and ball milling. Si-SiOx nanoparticles were doped into phenolic resin pyrolysis carbon as anode materials for lithium ion batteries, and 10% doping was observed to improve the specific capacity. After 500 cycles, specific capacity of delithiation remained around 550 mA h/g. It suggests the residual Si is a value-added by-product, and it can be recycled as anode materials for lithium ion batteries.